CRANIOSYNOSTOSIS: ACROCEPHALOSYNDACTYLY (APERT SYNDROME) DIAGNOSED IN A NEWBORN - Orhideja Stomnaroska; Dragan Danilovski; Sanja Ivanovska (Macedonian Academy of Sciences and Arts / Sciendo, 2017)
We report a 10 days old newborn with brachycephaly, midfacial hypoplasia, syndactyly and broad distal phalanx of thumb and big toe. At the 20th gestational weeks an enlargement of the left cerebral ventricle and malformation of the fingers of the hands and toes were noticed on a regular ultrasound examination. The aforementioned malformations were observed at birth and at the age of 11 months. The large fontal was closed; the small one was palpable at the tip of the finger. Brachycephaly was evident with high full forehead, flat occiput, and irregular craniosynostosis especially at the coronal suture. Cutaneous syndactyly was present at both hands (fingers II-V), with almost complete fusion of the second, third and fourth fingers. Distal phalanges of the thumbs were broad as well as distal hallux. There was cutaneous syndactyly of the feet. Mental development at the age of 11 months was normal. Apert syndrome is a sporadic disorder. Rarely, inheritance is autosomal dominant. Appropriate management includes surgical treatment of the syndactylies, follow up of the eventual airway compromise and hearing difficulties. This is a report of a patient identified as a newborn.
Keywords: cranyosynostosis; syndroma Apert; newborn